Professional stress levels among healthcare workers of Nelamangala: a cross sectional study - Sagar, Spoorthy; K. S., Ravish; T. S., Ranganath; Ahmed, Mohammed Tanveer; D., Shanmugapriya (International Journal Of Community Medicine And Public Health, 2017)
Background: Occupational stress can impair one’s health and reduce the efficiency and productivity of work. Delivering health services in rural areas is a tedious job for healthcare workers due to various factors. Inadequate staffing of workers leading to overloaded work and many other factors make them less motivated and experience work stress. Methods: A cross sectional study done in Nelamangla, rural field practice area of BMCRI. A multi stage random sampling technique was applied for the study. 5 PHCs were randomly chosen. Healthcare workers (such as LHV, ANM, Health Assistants, ASHA workers and AWWs) were recruited by probability proportion to sample size. 140 study participants were interviewed using pre tested semi structured questionnaire to collect socio demographic details and work related details; validated professional life stress scale was used to assess stress levels. Descriptive statistics and chi square test were used. Results: 37.1% (52) had mild stress, 52.1% (73) were moderately stressed, 10.7% (15) were severely stressed and none of them were very severely stressed that needed immediate intervention. Working hours, job satisfaction, clarity about work, amount of work exceeding stipulated time, loss of interest at work, not being rewarded and valued for their work are few of the factors that are found to be associated with stress levels. Conclusions: Work related factors have been the main stressors and higher stress levels might impede the performance of the workers and hence addressing this is necessary.